Charting the course: embracing challenges and anticipating future trends in building AI capacity for marketing excellence in emerging markets - Septeanny, Putrisia; Sulungbudi, Brigita Meylianti; Alijoyo, Franciskus Antonius (AMAR (Andalas Management Review), 2024)
The marketing landscape is undergoing a profound transformation with the emergence of artificial intelligence as a game-changer in driving innovation and customer engagement. Businesses are strategically integrating AI-powered solutions into their marketing decision-making to gain a competitive edge. Marketers are increasingly recognizing the immense potential of AI in enhancing their ability to identify competitors, understand customer preferences, and uncover valuable insights. The application of AI in marketing spans intelligent content generation, predictive analytics, personalized customer experiences, and automated campaign optimization. However, successful implementation of AI in marketing comes with its own set of challenges. This study aims to explore the evolving dynamics of AI in marketing, delve into its transformative impact, and identify key considerations for businesses looking to effectively harness this technological revolution by embracing challenges and anticipating new trends in AI adoption for achieving excellence in emerging markets.